(untitled) - Fielding, Helen (New York, 1999)
At the end of Bridget Jones's Diary, Bridget hiccuped off into the sunset with man-of-her-dreams Mark Darcy. Now she discovers what it is like when you have the man of your dreams actually in your flat and he doesn't do the washing up, not just the whole of this week, but ever.
Keywords: Humorous stories,Diary fiction,Những câu chuyện hài hước,Nhật ký tiểu thuyết